Knowledge, perception, and uptake of cervical cancer screening among women attending antenatal clinic at a tertiary hospital in north eastern Nigeria - Jomusu, Cyril A.; Noel, Nathaniel B.; Abubakar, Umar; Bakari, Maisaratu A.; Ameen, Hafsat A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This study assessed the knowledge, perception, and uptake of cervical cancer screening among women attending the antenatal clinic in Modibbo Adama University Teaching Hospital Yola, Nigeria. Methods: This was a cross-sectional study among 141 ante-natal clinic clients where data was collected using an interviewer-administered questionnaire. Data collected were analyzed using the IBM SPSS software. Multivariable logistic regression was used to determine the predictors of the uptake of cervical cancer screening. A p value of <0.05 was considered statistically significant. Results: Thirty-six (25.5%) respondents had good knowledge of cervical cancer screening, 12 (9%) had a positive perception of cervical cancer screening, and 14 (9.9%) had previously undergone screening. Health worker request was the major reason for undertaking screening while lack of awareness of the screening was the chief reason for not screening previously. Multivariable logistic regression showed knowledge to be the only predictor of the uptake of cervical cancer screening, respondents with good knowledge were about six times more likely (AOR: 5.97, 95% CI: 1.57-22.66, p=0.009) to have ever been screened. Conclusions: The predominantly poor knowledge, negative perception, and poor uptake of cervical cancer screening in this study suggest the need to improve clients’ education to boost the uptake of screening services.